Effect of selenium biofortification on bioaccessibility, antioxidant, and antimicrobial potentials of phenolic compounds in germinated black soybean (Glycine max (L.) Merr). Issue 6 (18th September 2022) - Huang, Junyi; Yang, Jingyi; Miao, Qianqian; Olajide, Tosin Michael; Qian, Jiana; Liu, Haoyue; Ou, Pengcheng; Liao, Xianyan
Abstract: Background and Objective: Biofortification with inorganic selenium has become a key strategy to enhance selenium content in crops. This study aimed to investigate the changes of phenolic compounds and their effects on antimicrobial and antioxidant activities during in vitro digestion of selenium biofortified germinated black soybeans (GBS‐Se). Findings: The bioaccessibility of total polyphenols and total flavonoids in GBS‐Se were significantly lower than those of germinated black soybeans (GBS). p ‐Coumaric acid and salicylic acid in GBS‐Se and GBS increased significantly in the oral phase; syringic acid and benzoic acid were the main phenolic acids in the gastric phase, while phenolic acids decreased continuously in the intestinal phase. There was some minor difference between the antioxidant activities of GBS‐Se and GBS in vitro digested products, but their 2, 2'‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) (ABTS) scavenging and ferric reducing antioxidant power reducing capacities increased compared with those before digestion. In addition, inhibitory effects on Escherichia coli and Staphylococcus aureus were observed only in undigested black soybean phenolic extracts. Conclusions: Selenium fortification affected the phenolic compounds and their bioaccessibility of GBS, which should be considered in nutrition research. Significance and Novelty: These results could help systematically evaluate the effect of selenium fortification on the digestibility of phenolic compounds in GBS and provide a reference for the development and application of Se‐enriched functional foods.